2022
DOI: 10.48550/arxiv.2202.13806
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parameter estimation and model reduction for retinal laser treatment

Abstract: Laser photocoagulation is one of the most frequently used treatment approaches for retinal diseases such as diabetic retinopathy and macular edema. The use of model-based control, such as Model Predictive Control (MPC), enhances a safe and effective treatment by guaranteeing temperature bounds. In general, real-time requirements for model-based control designs are not met since the temperature distribution in the eye fundus is governed by a heat equation with a nonlinear parameter dependency. This issue is cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In our previous work [10], we performed a parameter study with 250 treatment spots and obtained the empirical means ᾱrpe = 0.7636 and ᾱch = 0.0986 and the empirical standard deviations σ rpe = 0.1907 and σ rpe = 0.0281, respectively. Thus, the parameter domain that was used for parametric model reduction and that will be used in the MHE in Subsec.…”
Section: Modeling and Model Order Reductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work [10], we performed a parameter study with 250 treatment spots and obtained the empirical means ᾱrpe = 0.7636 and ᾱch = 0.0986 and the empirical standard deviations σ rpe = 0.1907 and σ rpe = 0.0281, respectively. Thus, the parameter domain that was used for parametric model reduction and that will be used in the MHE in Subsec.…”
Section: Modeling and Model Order Reductionmentioning
confidence: 99%
“…We consider two different scenarios: first, a simpler one where the absorption coefficient in the choroid is assumed to be constant and only the absorption coefficient in the RPE is estimated. This is motivated by our case study [10], which showed that the inputoutput sensitivity is higher with respect to the RPE absorption coefficient than to the choroid absorption coefficient. In a second scenario, both absorption coefficients of the RPE and the choroid are estimated independently.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations